Cognitive Development Analysis of Dyslexia Children in Madrasah Ibtidaiyah Al-Ma’rif Cirebon During the Covid 19 Pandemic - ZulfiIdayanti; Afiyatunnufus; Kamala, Izzatin (Proceeding International Conference on Religion, Science and Education, 2022)
The success of the teaching and learning process for students with dyslexia can be achieved if the learning program is structured based on the potential and needs of students. Unfortunately, the learning process for dyslexic students in one of the MIs in Cirebon City has not been adjusted so that student achievement is not visible. The purpose of this study was to determine the cognitive development of dyslexic children during the Covid 19 pandemic. This research is a qualitative type with a case study method to analyze cognitive abilities in dyslexic children. The research subject was a grade 6 dyslexic student at MI Al-Ma’arif Cirebon. Data collection techniques using observation, interviews, documentation and reading tests. The results showed that students with dyslexia tend to have lower reading abilities than other students. This is due to their slow cognitive abilities resulting in difficulty spelling, distinguishing letters b, d, p and q, difficulty remembering and concentrating, learning programs that are not suitable for dyslexic children and the absence of special companion teachers for dyslexic students.